2017
DOI: 10.26487/hebr.v1i2.1250
|View full text |Cite
|
Sign up to set email alerts
|

Board Structure and Earnings Management: Evidence of South East Asia Countries Categorised by Agency Cost Level

Abstract: Agency theory infers that investors will incur cost to make alignment on principal-agent interest. A critic, however, has pointed out that the conflict of interest between principal and agent is not the only cause for agency cost. Cultural context (Johnson & Droege, 2004) and legal system (La Porta, et al., 2000) are also found as contributing factors. This study is to empirically investigate how board size, board independency, audit committee size and audit committee independency affect the earnings quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Teori agensi diperkenalkan oleh Jensen & Meckling (1976) yang memaparkan hubungan keagenan sebagai kontrak kerja pendelegasian wewenang dari pemilik perusahaan (principal) kepada pihak lain yang dipekerjakan (agent). Di negara-negara berkembang kepemilikan saham cenderung terkonsentrasi dan konflik tata kelola perusahaan sebagian besar timbul kepada pemegang saham mayoritas dengan pemegang saham minoritas (Banchit Novitasari, Putra & Locke, 2016;Chen & Young, 2010;Putra & Arif, 2017;Young et al, 2008). Konflik principal-principal tersebut terjadi ketika pemegang saham mayoritas menggunakan kekuatan suara mereka untuk mengontrol perusahaan dan mengambil manfaat pribadi dari kontrol tersebut (Banchit & Locke, 2016;Renders & Gaeremynck, 2012).…”
Section: Tinjauan Literatur Dan Pengembangan Hipotesis Teori Agensiunclassified
“…Teori agensi diperkenalkan oleh Jensen & Meckling (1976) yang memaparkan hubungan keagenan sebagai kontrak kerja pendelegasian wewenang dari pemilik perusahaan (principal) kepada pihak lain yang dipekerjakan (agent). Di negara-negara berkembang kepemilikan saham cenderung terkonsentrasi dan konflik tata kelola perusahaan sebagian besar timbul kepada pemegang saham mayoritas dengan pemegang saham minoritas (Banchit Novitasari, Putra & Locke, 2016;Chen & Young, 2010;Putra & Arif, 2017;Young et al, 2008). Konflik principal-principal tersebut terjadi ketika pemegang saham mayoritas menggunakan kekuatan suara mereka untuk mengontrol perusahaan dan mengambil manfaat pribadi dari kontrol tersebut (Banchit & Locke, 2016;Renders & Gaeremynck, 2012).…”
Section: Tinjauan Literatur Dan Pengembangan Hipotesis Teori Agensiunclassified
“…Several studies have shown the problem of the Permanent Voter List (Kolamban et al, 2019;Putra & Hasanuddin, 2017;Sari et al, 2019;Supranto, 2021). These three studies found the fact that the problem of DPT in various regions in Indonesia was caused by the KPU's performance that had not been maximized.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2018 West Kalimantan gubernatorial election, there was also a DPT technical error (Supranto, 2021). Furthermore, in the 2015 Bengkalis Regency Regent election, it was also found that there was a problem with the negligence of the voter list updating officer so that the DPT was problematic (Putra & Hasanuddin, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations